BUDAYA PELA GANDONG SEBAGAI STRATEGI KOMUNIKASI KRISIS PENYELESAIAN KONFLIK AMBON - Graic Bectran Solissa; Justin Enrico Sapulete; Marco Thomas Berburu; Mariana Behuku; Solagratia Defindry Nanuru (JURNAL BADATI, 2023)
Domestic violence remains a serious social problem in Indonesia. The role of Non-Governmental Organizations (NGOs) in providing social assistance for domestic violence victims is crucial. This research aims to analyze the social assistance patterns developed by NGOs in handling domestic violence victims in Indonesia. Using a systematic literature review method, this study analyzed 45 pieces of literature published between 2018-2024. The results identified four main assistance patterns: psychosocial (35.5%), legal (28.3%), economic (21.2%), and medical (15%). The highest success rate was recorded in psychological recovery (75%), while economic independence still showed relatively low achievement (50%). Major challenges in program implementation include limitations in trained human resources (85%), funding (78%), and socio-cultural barriers (70-72%). This research recommends strengthening economic empowerment aspects, developing digital-based services, and improving multi-stakeholder coordination to optimize the effectiveness of assistance programs. The practical implications of this research contribute to the development of more effective and sustainable assistance models for domestic violence victims.